Development of multifunctional electrochemical membrane system for seawater desalination - Long, Wei (Nanyang Technological University, 2024)
The appropriate pH level is of great significance for a wide variety of industries and applications, particularly those related to water treatment. However, existing methods for adjusting pH, such as adding acid/base and using electrochemical processes, have drawbacks in terms of their impacts on the environment and energy consumption. In this regard, a multifunctional electrochemical membrane system (EMS) was designed to address these challenges. The EMS consists of a filtration membrane placed within an electrochemical cell. By applying an electrical field, reduction and oxidation reactions at cathode and anode generate OH- and H+ ions, respectively. The membrane acted as a barrier, impeding the transport and preventing the mixing of OH- and H+ ions in the cell. The EMS can be operated in both non-filtration and filtration modes. The filtration mode allows simultaneous regulation of permeate and feed pH while facilitating water filtration. Importantly, EMS achieves effective regulation of solution pH over a wide range without the need for chemical dosing by exerting different voltages. Solution pH levels of 10.7 and 3.3 could be achieved and maintained in cathodic and anodic channels, respectively, using a voltage of 1.2 V. Additionally, experimental results have shown that the EMS consumed minimal electrical energy. This, along with its integration with membrane filtration, highlights the enormous potential of EMS for various water applications. EMS was incorporated in the application of seawater desalination. In seawater desalination, the prevailing two-pass reverse osmosis (RO) process requires substantial chemical consumption to secure product water quality. For instance, caustic soda is used to raise the pH of the first-pass RO permeate (also the second-pass RO feed) to ensure adequate removal of boron in the subsequent second-pass RO by converting boric acid into borate ion with larger hydrated size and negative charge. Additionally, antiscalants and disinfectants, such as hypochlorite, are added in the feed seawater to control scaling and biofouling of the first-pass RO membranes. To dramatically reduce or even eliminate chemical usage for the current RO desalination, a flow-through electrochemically assisted reverse osmosis (FT-EARO) module system was developed to be used in the first-pass RO. The design FT-EARO is on the basis of EMS, which integrates with the seawater reverse osmosis (SWRO) membrane. Upon applying an extremely low-energy (< 0.005 kWh/m3) electrical field, the FT-EARO module could (1) produce a permeate with pH >10 with no alkali dosage, ensuring sufficient boron removal in the second-pass RO, and (2) generate protons and low-concentration free chlorine in the feed seawater, potentially mitigating scaling and biofouling while maintaining satisfactory desalination performance. While FT-EARO can dramatically reduce the chemical usage with minimal electrical energy consumption, it still requires the employment of second-pass RO process. Therefore, elimination of the second-pass RO can further significantly reduce energy consumption in the current seawater desalination plants. This can be accomplished by integrating EMS with pretreatment methods such as ultrafiltration (UF) and nanofiltration (NF) prior to the single-pass RO, with an increased pH of the pretreatment permeate. Under the electrical field, precipitations of divalent ions which transported through the UF membrane in the cathodic permeate channel would necessitate additional cleaning strategies. Nevertheless, the selection of an appropriate NF membrane enables efficient permeate (also used as feed to the SWRO unit) pH elevation above 9 without concerns about cathodic precipitation. The developed system, named flow-through electrochemically assisted nanofiltration (FT-EANF), serves as the pretreatment and could also reduce the usage of antiscalants and energy requirement in the subsequent SWRO unit, due to the dramatically decreased presence of divalent ions and salinity. This novel system could integrate an electroconductive permeate carrier as cathode and an electroconductive feed spacer as anode on each side of the RO or NF membrane. Therefore, the study further elucidated the high scalability of the novel electrified high-pressure RO and NF module design. The chemical-free and low-energy manner of FT-EARO and FT-EANF pretreatment presents an attractive practical option towards green, energy-efficient and sustainable seawater desalination.